2020
DOI: 10.1007/s00253-020-10945-w
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori treatment in the post-antibiotics era—searching for new drug targets

Abstract: Helicobacter pylori, a member of Epsilonproteobacteria, is a Gram-negative microaerophilic bacterium that colonizes gastric mucosa of about 50% of the human population. Although most infections caused by H. pylori are asymptomatic, the microorganism is strongly associated with serious diseases of the upper gastrointestinal tract such as chronic gastritis, peptic ulcer, duodenal ulcer, and gastric cancer, and it is classified as a group I carcinogen. The prevalence of H. pylori infections varies worldwide. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 148 publications
0
87
0
Order By: Relevance
“…It should be mentioned that gastric cancer is the third most deadly cancer in the world [ 1 ]. One of the risk factors confirmed for gastric cancer is infection with the bacterium H. pylori [ 2 , 3 , 4 , 5 , 6 ], which is a spiral-shaped Gram-negative bacterium that infects more than half of the world’s population [ 2 , 7 , 8 ]. This bacterium colonizes the gastric mucosa and the surfaces of the gastric epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that gastric cancer is the third most deadly cancer in the world [ 1 ]. One of the risk factors confirmed for gastric cancer is infection with the bacterium H. pylori [ 2 , 3 , 4 , 5 , 6 ], which is a spiral-shaped Gram-negative bacterium that infects more than half of the world’s population [ 2 , 7 , 8 ]. This bacterium colonizes the gastric mucosa and the surfaces of the gastric epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Lender et al found a negative association between Hp infection and BMI level 31 . Hp infection could cause a series of gastric diseases, such as chronic gastritis 32 , and then lead to GC eventually 33 . When infected with Hp , subjects might suffer from chronic gastritis and other gastric diseases for a long time, even more than 10 years, which could cause their weight loss by affecting food intake or digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The search for new drugs displaying activity against H. pylori is now a hotspot in the effective and safe control of this bacterium [ 11 ]. High hopes are associated with phytotherapy, which is the practice of using raw or processed plant products (flowers, leaves, stalks, roots, or seeds) for medicinal purposes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%